Neuromuscular monitoring during modified rapid sequence induction: A comparison of TOF-Cuff® and TOF-Scan®. (December 2020) - Chau, Ivan; Horn, Katja; Dullenkopf, Alexander
Abstract: Background: Acceleromyometry is the clinical standard for quantitative neuromuscular monitoring, mostly using the stimulation pattern train-of-four (TOF). TOF-Cuff®, a recently introduced neuromuscular monitor with stimulating electrodes integrated within a blood pressure cuff, assesses the muscular response in the upper arm. Methods: The time from administration of a neuromuscular blocking agent to TOF-ratio 0% during modified rapid sequence induction was compared between TOF-Cuff® and acceleromyometry (TOF-Scan®). Included were 26 adults with body mass index <35 kg/m 2 . TOF-Scan® and TOF-Cuff® were simultaneously fitted on patients' opposite arms. The mean difference to TOF-ratio 0% was compared using the one sample t -test (p < 0.05) and Bland–Altman plots. Results: After anesthesia induction, atracurium 0.9 mg/kg (±0.08) i.v. was administered. The mean time to TOF ratio 0% for TOF-Scan® was 140.4 s (±34.3), and 132.7 s (±32.5) for TOF-Cuff®, with a mean difference of 5.4 (95% CI: −9.9 to 20.7, p = 0.472). The maximum difference between the two modalities was 135 s when the TOF-Cuff® was faster and 60 s when the TOF-Scan® was faster. Conclusions: No statistically significant systematic difference was found between TOF-Scan® and TOF-Cuff®. However, there was high variability and wide limits of agreement. The two devices cannot be used interchangeably.